Feasibility study for supporting medication adherence for adults with cystic fibrosis: mixed-methods process evaluation. Issue 10 (27th October 2020) - Hind, Daniel; Drabble, Sarah J; Arden, Madelynne A; Mandefield, Laura; Waterhouse, Simon; Maguire, Chin; Cantrill, Hannah; Robinson, Louisa; Beever, Daniel; Scott, Alex; Keating, Sam; Hutchings, Marlene; et al.
Abstract : Objectives: To undertake a process evaluation of an adherence support intervention for people with cystic fibrosis (PWCF), to assess its feasibility and acceptability. Setting: Two UK cystic fibrosis (CF) units. Participants: Fourteen adult PWCF; three professionals delivering adherence support ('interventionists'); five multi-disciplinary CF team members. Interventions: Nebuliser with data recording and transfer capability, linked to a software platform, and strategies to support adherence to nebulised treatments facilitated by interventionists over 5 months (± 1 month). Primary and secondary measures: Feasibility and acceptability of the intervention, assessed through semistructured interviews, questionnaires, fidelity assessments and click analytics. Results: Interventionists were complimentary about the intervention and training. Key barriers to intervention feasibility and acceptability were identified. Interventionists had difficulty finding clinic space and time in normal working hours to conduct review visits. As a result, fewer than expected intervention visits were conducted and interviews indicated this may explain low adherence in some intervention arm participants. Adherence levels appeared to be >100% for some patients, due to inaccurate prescription data, particularly in patients with complex treatment regimens. Flatlines in adherence data at the start of the study were linked to device connectivity problems. Content and delivery quality fidelity were 100% and 60%–92%, respectively, indicating that interventionists needed to focus more on intervention 'active ingredients' during sessions. Conclusions: The process evaluation led to 14 key changes to intervention procedures to overcome barriers to intervention success. With the identified changes, it is feasible and acceptable to support medication adherence with this intervention. Trial registration number: ISRCTN13076797; Results.